Budidaya Tanaman Jambu Mete Dan Pemasaran Dalam Meningkatkan Pendapatan Masyarakat Desa Hokeng Jaya - Yosef Moan Banda (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
The purpose of this study was to reveal the existence of cashew cultivation in increasing income, as well as the amount of community income from cashew sales and the factors supporting and inhibiting cashew cultivation. The focus of the problem is that cashew plants receive less attention from cashew farmers. This type of research is an integrated quantitative and qualitative research. An integrated quantitative and qualitative descriptive research approach. Collecting data with three techniques, namely